EcoSmart Energy and Health Care Promotion in Senior Tourism - Amila Pilav-Velic; Nedim Suta; Anes Hrnjic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Recent studies show that seniors will soon become one of the major prospective segments in hospitality and travel industry. Given that population aged 65+ is usually retired with pensions, they have leisure time for travelling at any time of the year. They are also the most demanding expecting services excellence and high-level security while at the same time 63% of seniors aged 65-74 reported some sort of chronic illness. Hence, energy-efficient and health-focused facilities can be a significant potential for tourism development in Sarajevo region, which is a popular destination considering its unique nature, rich gastronomic, cultural and historical heritage. However, currently there is no market segmentation tailored to specific needs of senior tourists and research aims to explore opportunities and potential for this type of services with the objective of introducing accommodation facilities for elderly based on eco-smart solutions with highlighted focus on well-being and health. Setting of still water machines and installation of renewable energy system for electricity, ventilation and heat can have various positive effects increasing security, providing more healthy conditions, influencing life expectancy and counteracting the aging. Thus, research goal is creating feasibility study on eco-smart and healthfocused facility for senior tourists in Sarajevo region using strategic management tools as a methodology instruments, including application of PEST concept, determining industry development phase as well as evaluating its structure, attractiveness and profitability via five forces of Porter model. Recommendations for future studies as well as practical implications for appropriate business actions are given in the conclusion relating to senior tourism development in Sarajevo region.
Keywords: L83; Q57; O13; 330; senior tourism; eco-smart energy; health care; sustainable development